Social Relations of Village Communities to the Development of Artificial Intelligence - Sholichin, Riyadus (Proceeding International Conference on Religion, Science and Education, 2024)
The rapid development of digital technology cannot be avoided. Because digital technology develops according to the times. This development also has an impact on rural communities. However, this development cannot be said to be successful. This is because access to digital technology is still massive among rural communities. Where local village communities find it very difficult to accept developments in digital technology. In addition, rapidly developing artificial intelligence is making rural communities increasingly left behind. So this research aims to see the extent of the impact of artificial intelligence on village communities. Apart from that, how do village communities respond to technology, especially artificial intelligence? The findings of this research are on efforts to protect consumer data against artificial intelligence. Where social relations have an important role to play in protecting personal data. This research uses a literature study method by compiling from writings related to the topic to be discussed. Data collection techniques were obtained from library sources in the form of books, scientific journals and relevant proceedings. Next, the researcher examines the focus of literature observations by looking for relevant data according to the topic of discussion. Then present it in detail through primary and secondary literature sources related to the topic discussed. Thus, it is hoped that the results of this research can provide an understanding of digital technology. Village community concerns regarding the development of artificial intelligence must be actively addressed. Apart from maintaining personal safety, this understanding effort can have an impact on the social roles of fellow villagers.